First-year secondary school mathematics students' conceptions of mathematical proofs and proving - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
The aim of this study is to investigate students' conceptions about proof in mathematics and mathematics teaching. A five-point Likert-type questionnaire was administered in order to gather data. The sample of the study included 33 first-year secondary school mathematics students (at the same time student teachers). The data collected were analysed and interpreted using the methods of qualitative and quantitative analysis. The results have revealed that the students think that mathematical proof has an important place in mathematics and mathematics education. The students' studying methods for exams based on imitative reasoning which can be described as a type of reasoning built on copying proof, for example, by looking at a textbook or course notes proof or through remembering a proof algorithm. Moreover, they addressed to the differences between mathematics taught in high school and university as the main cause of their difficulties in proof and proving.
Keywords: mathematical proof; mathematics teaching; students' conceptions